(untitled) (Journal of the College of Education for Women, 2019)
Abstract:The problem of the research is that the person face in the starting of hisprofession life is to go to the right profession that he or she fits in when theperson enter the works sea many problems appear to him on of them is hisnon-accordance with his job ,the research targeted to know the levels of theaccordance of the kindergarten teachers and the relation between theprofession accordance and other like the kind of level and the time of serviceand the research worked with (150) kindergarten teachers from theintroductory class and (150) kindergarten teachers from the kindergarten classfor the study year 2008-2009 .The research been made a measure to get the goal of the research afterthe pull out of the honesty and the prove and it prove coefficient is (0.82)andthe researcher use for the test for one sample and two sample and theconnection coefficient person to find the honesty builder and the Alfa equationand bilateral analyzing to distinguish the difference in the professionaccordance within the time of the service and the level and the result showedthat profession accordance for the persons of the research and there is nodifference a statistic intimacy in the profession accordance within the changesof the levels (kindergarten ,introductory) while there is a difference of astatistic intimacy in the changes of service time. At last the researcher pull outsome recommendations and proposals